THE IMPACT OF USING AI WITHOUT ADEQUATE ENGLISH PROFICIENCY AMONG USERS IN MATARAM: Dampak Penggunaan AI Tanpa Kemampuan Bahasa Inggris yang Memadai di Kalangan Pengguna di Mataram - I Gusti Ngurah Octova Seventilofa (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The use of artificial intelligence (AI) is rapidly increasing across various societal activities, including in Mataram—although most users do not have adequate English proficiency. This study aims to analyze issues arising from AI usage by users with limited English skills. Employing quantitative methods (survey of 120 users) and qualitative methods (15 in-depth interviews), we examine phenomena such as miscommunication, AI bias, and socio-ecological impacts. Data show that 68% experienced misconceptions about AI outputs, 60% faced verbal discrimination, and 52% received inaccurate information. These results are reinforced by techno-linguistic bias and AI’s tendency to favor Standard English. Recommendations include language training, development of local bilingual AI, and inclusive policies. The findings raise awareness that language proficiency is an important prerequisite for fair and effective AI adoption